Detecting Diabetic Neuropathy From Electronic Health Records Using Machine Learning - Dehkordi, Zahrasadat Solati (2023)
A Master of Science thesis in Computer Engineering by Zahrasadat Solati Dehkordi entitled, “Detecting Diabetic Neuropathy from Electronic Health Records Using Machine Learning”, submitted in April 2023. Thesis advisor is Dr. Salam Dhou. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).